Compiling the First Monolingual Lusoga Dictionary - Nabirye, Minah (Lexikos, 2009)
Abstract: In this research article a study is made of the approach followed to compile the first-ever monolingual dictionary for Lusoga. Lusoga is a Bantu language spoken in Uganda by slightly over two mil-lion people. Being an under-resourced language, the Lusoga orthography had to be designed, a grammar written, and a corpus built, before embarking on the compilation of the dictionary. This compilation was aimed at attaining an academic degree, hence requiring a rigorous research methodology. Firstly, the prevail-ing methods for compiling dictionaries were mainly practical and insufficient in explaining the theoretical linguistic basis for dictionary compilation. Since dictionaries are based on meaning, the theory of meaning was used to account for all linguistic data considered in dictionaries. However, meaning is considered at a very abstract level, far removed from the process of compiling dictionaries. Another theory, the theory of modularity, was used to bridge the gap between the theory of meaning and the compilation process. The modular theory explains how the different modules of a language contribute information to the different parts of the dictionary article or dictionary information in general. Secondly, the research also had to contend with the different approaches for analysing Bantu languages for Bantu and European audiences. A descrip-tion of the Bantu- and European-centred approaches to Bantu studies was undertaken in respect of (a) the classification of Lusoga words, and (b) the specification of their citations. As a result, Lusoga lexicography deviates from the prevailing Bantu classification and citation of nouns, adjectives and verbs in particular. The dictionary was tested on two separate occasions and all the feedback was considered in the compilation pro-cess. This article, then, gives an overall summary of all the steps involved in the compilation of the Eiwanika ly’Olusoga, i.e. the Monolingual Lusoga Dictionary. Keywords: LEXICOGRAPHY, MONOLINGUAL DICTIONARY, THEORETICAL FRAMEWORK,DICTIONARY TESTING, EURO-CENTRED, BANTU-CENTRED, ORTHOGRAPHY,GRAMMAR, WORD CLASSES, BANTU LANGUAGES, LUSOGA, UGANDA Obufunze: Okuwandiika Eiwanika ly’Olusoga Elyasookela Ilala. Mu kiwandiikokino mulimu ennambulula y’eisomo elyasinziilwaku okuwandiika eiwanika ly’Olusogaelisookeile ilala. Olusoga lugwa mu nnimi dh’ekika kya Bantu ela lwogelwa abantu abaswika mubukaile obubili mu Uganda. Engeli Olusoga ye lwali nga ti lugundhiivu bulungi mu buwandiike,kyali kyetaagisa okwekalilisa walifu y’Olusoga, okuwandiika gulaama n’okuzimba eitelekeloly’ebiwandiiko ebisinziilwaku okuwandiika Olusoga. Okuwandiika eiwanika lino kwali kilala kubigendelelwa by’omusomo gw’omuwandiisi. Noolwekyo engeli y’okunoonheleza ku byetaagisayalina okuba nga yeetengelela ku mutindo gw’obwevu. Okusookela ilala empandiika y’amawanikaebailewo ebaile esinga kulaga omulimu ogukoleibwa aye ng’engeli gye gutuukiibwaku teinhonholwabukalamu. Amawanika gasinga kulondoola ntegeelo dha bigambo ela omusingi gw’entegeelon’ogwalina okwesigamibwaku okusobola okufuna ebyetaagibwa mu mawanika. Kimanhibwe nti entegeelo dh’ebigambo dheesigama ku mbeela y’olulimi enneekusifu nga tetegeelekekamangu ku idaala ly’okuwandiika amawanika. Noolwekyo omusingi ogundi ogwesigaime kumitendela egyekalilisibwaku olulimi n’ogwakozesebwa okugaitania omusingi gw’entegeelo kumitendela gy’okuwandiika amawanika. Emitendela egyekalilisibwaku olulimi giinhonhola engeliemitendela egy’endhawulo bwe gikolagana okusobola okutuuka ku bitundu by’eiwanika. Ekyokubili,okunoonheleza kuno ela kwalina okwekalilisa engeli ennimi dh’ekika kya Bantu bwe dheeyolekaeli beene nnimi n’abo abagwila abenda okudheega. Okwawula n’okugelaagelania engeliennimi dha Bantu bwe dheeyoleka eli ebika by’abantu bano ab’endhawulo yakolebwa mu (a)emmindhawaza y’ebigambo ni (b) okusalawo engeli ebigambo by’eiwanika bwe bilina okwingizibwa.Oluvainhuma lwa byonabyona empandiika y’amawanika mu Lusoga yakyusa mu ngeliedhibailewo ey’okubindhawaza ebigambo okusingila ilala embu dha naliina, nambeela, nikinantabila. Eiwanika ly’Olusoga lyagezesebwa emilundi ebili ela ebyava mu kugezesebwa kunobyafulumila mu Eiwanika. Olupapula luno n’olulaga mu bufunze omusingi ogwasinziilwakuokuwandiika Eiwanika ly’Olusoga. Ebigambo ebikulu: EMPANDIIKA Y’AMAWANIKA, EIWANIKA ELY’OLULIMI OLULALA,OMUSINGI GW’OKUNOONHELEZA, OKUGEZESA EIWANIKA, AMASOMO AGEEKUUSAKU BULAAYA, AMASOMO AGEEKUUSA KU AFRIKA, WALIFU, GULAAMA, EMBUDH’EBIGAMBO, ENNIMI DHA BANTU, OLUSOGA, UGANDA